THE RELATIONSHIP BETWEEN EXTERNAL DEBT AND ECONOMIC GROWTH IN POST-SOVIET ECONOMIES - Shavkatjonov Mardon Zokirjon ugli; Gulyamova Gulshaxnoz Sabirovna (Modern American Journals, 2025)
This article examines the complex relationship between external debt and economic growth in post-Soviet economies. By combining theoretical perspectives with empirical analysis, it evaluates how debt accumulation affects macroeconomic performance in these transitioning nations. Utilizing panel data from international financial institutions, the research applies econometric models to quantify the impact of external debt on GDP growth. The findings offer critical insights for policymakers, highlighting the need to strike a balance between debt sustainability and economic development, ensuring long-term financial stability and growth in the region.
Keywords: External debt, economic growth, post-soviet economies, debt sustainability, GDP growth, debt-to-GDP ratio, debt management, transition economies, financial stability, foreign borrowing.